Subjective well being in adolescences on Minangkabau ethnic; an analysis based of dimension and gender - Berru Amalianita; Herman Nirawana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to analyze the subjective well-being of adolescents in Minangkabau ethnicity. There are 182 participants of Minang adolescencets. The method in this study used a quantitative descriptive approach. The research instrument uses a subjective well being scale that has been tested for validity and reliability. The data analysis technique used descriptive statistics and boxplot analysis used the JAPS (Jeffrey's Amazing Statistics Program) application. The result showed that the subjective well being Minangkabau adolescents were in the high category, based on the subjective well being dimension, the dominant life statistic was in the high category and the affective dimension was in the medium category. Then based on gender, there is no significant difference in subjective well being of adolescent men and woman. This shows that the subjective well-being condition of Minangkabau adolescents is high as well as in each of its dimensions, both cognitive and affective. This condition needs to be optimized through various parties so that Minangkabau adolescents have good subjective well-being and avoid maladaptive behavior.